Sistem Pendukung Keputusan Pemilihan Objek Wisata Kabupaten Berau Menggunakan Metode Additive Ration Assessment (ARAS) - Lengkong, Mira S.; Dengen, Nataniel; Agus, Fahrul (Fakultas Teknik Universitas Persada Indonesia YAI, 2025)
Indonesia is a country that is famous for its natural wealth and tourist destinations worldwide, and it is spread out in various regions. One of the regions in East Kalimantan that is popular and often visited by tourists every year because it is famous for its stunning underwater tourist destinations is the Berau Regency. According to the East Kalimantan Tourism Office, this district has the highest number of tourist attractions in East Kalimantan, which is 224. Many tourist attractions trigger confusion among tourists when deciding which alternative option to visit. Therefore, this research aims to build a decision support system to assist tourists in getting alternative tourism recommendations that are appropriate and to their needs. The method used in this research is the Additive Ratio Assessment (ARAS) method. There are 30 alternative attractions and 5 criteria: facilities, safety, cleanliness, cost, and distance. The results show that the ARAS method can recommend the best alternative to tourist attractions. The accuracy testing results using the confusion matrix method get a percentage value of 80%.